Insulin resistance is associated with liver stiffness in HIV/HCV co-infected patients. Issue 12 (21st July 2009) - Merchante, N; Rivero, A; de los Santos-Gil, I; Merino, D; Márquez, M; López-Ruz, M Á; Rodríguez-Baño, J; del Valle, J; Camacho, Á; Sanz-Sanz, J; Macías, J; Pérez-Camacho, I; et al.
Abstract : Background: The factors that influence liver fibrosis progression in patients co-infected with human immunodeficiency virus/hepatitis C virus (HIV/HCV) are not completely understood. It is not known if insulin resistance (IR), a condition that promotes liver fibrosis in HCV mono-infected individuals, is one of these factors. Objective: To evaluate the association between IR and liver stiffness (LS). Design: Multicentre cross-sectional study. Patients: 330 patients co-infected with HIV/HCV. Methods: LS was assessed by transient elastography, which has shown a high accuracy to predict significant fibrosis in patients co-infected with HIV/HCV. The outcome variable of the study was LS. Patients with LS⩾9 kPa were considered as having significant fibrosis. IR was calculated using the HOMA method. Results: LS was ⩾9 kPa in 150 (45%) patients. HOMA correlated with LS (Spearman's rho correlation coefficient, 0.37; p<0.0001). The median (Q1–Q3) HOMA in patients with LS⩾9 kPa was 3.30 (2.17–5.16) while it was 2.09 (1.37–3.22) in patients with LS <9 kPa (p<0.0001). Ninety-six (39%) individuals with a HOMA <4 and 54 (63%) with a HOMA ⩾4 showed LS⩾9 kPa (p<0.0001). Analyses after excluding patients with cirrhosis yielded similar results. After multivariate analyses, age ⩾40 years (adjusted odds ratio (AOR), 1.85; 95% confidence interval (CI), 1.03 to 3.29; p = 0.03), CD4 cell count <200 cells/ml (AOR, 3.45; 95% CI, 1.67 to 7.11; p = 0.001), hepatitis B virus co-infection (AOR, 9.25; 95% CI, 2.42 to 35.31; p = 0.001), and HOMA ⩾4 (AOR, 5.33; 95% CI, 2.70 to 10.49; p<0.0001) were the independent predictors of LS⩾9 kPa. Conclusion: IR is associated with LS in patients co-infected with HIV/HCV.